2008
DOI: 10.1007/s00432-008-0412-4
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-based identification of CUB-domain containing protein 1 as a potential prognostic marker in conventional renal cell carcinoma

Abstract: We identified CDCP1 as a potential prognostic marker for conventional RCC. Further studies might be required to confirm the prognostic value of CDCP1 and to understand its function in RCC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 27 publications
(33 reference statements)
2
66
0
Order By: Relevance
“…CDCP1 expression is positively correlated with poor prognosis in patients with lung, renal, or pancreatic cancer (8)(9)(10). These findings strongly suggest that CDCP1 promotes cancer metastasis and invasion.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…CDCP1 expression is positively correlated with poor prognosis in patients with lung, renal, or pancreatic cancer (8)(9)(10). These findings strongly suggest that CDCP1 promotes cancer metastasis and invasion.…”
Section: Discussionmentioning
confidence: 75%
“…The expression of CDCP1 was reported in several human malignancies, such as colon and breast cancers (3,7). CDCP1 expression is strongly associated with cancer progression and poor prognosis in renal cell carcinoma, lung adenocarcinoma, and pancreatic cancer (8)(9)(10). We previously reported that CDCP1 is a critical regulator of anoikis resistance in lung cancer cells (11), peritoneal dissemination of gastric scirrhous carcinoma (12), and invasion of pancreatic cancer cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…In several tumor types that commonly metastasize via vascular routes, including lung, kidney, pancreas and colon cancer, elevated or cell-surface expression of CDCP1 is associated with poor patient outcome. [12][13][14][15][16][17] Consistent with a role in hematogenous metastasis, in animal models of vascular dissemination, survival of cancer cells undergoing extravasation is markedly enhanced by a mechanism involving serine protease cleavage to generate 70 kDa CDCP1. This initiates pro-survival signaling via focal adhesion kinase 1 and phosphoinositide 3-kinase (PI3K) dependent protein kinase B (Akt) activation resulting in suppression of poly (ADP-ribose) polymerase 1 (PARP1) mediated apoptosis.…”
Section: Introductionmentioning
confidence: 92%
“…Four studies assessed the possibility of using the level of CDCP1 expression as a prognostic factor for survival of lung adenocarcinoma, conventional RCC, pancreatic cancer patients, and endometrioid adenocarcinoma (29,(32)(33)(34). All of them indicated that elevated CDCP1 expression correlates with low overall survival.…”
Section: Cdcp1 Expression On the Cell Surface Of Tumor Cells Correlatmentioning
confidence: 99%